1994
DOI: 10.2307/2329272
|View full text |Cite
|
Sign up to set email alerts
|

Why do NASDAQ Market Makers Avoid Odd-Eighth Quotes?

Abstract: The NASDAQ multiple dealer market is designed to produce narrow bid‐ask spreads through the competition for order flow among individual dealers. However, we find that odd‐eighth quotes are virtually nonexistent for 70 of 100 actively traded NASDAQ securities, including Apple Computer and Lotus Development. The lack of odd‐eighth quotes cannot be explained by the negotiation hypothesis of Harris (1991), trading activity, or other variables thought to impact spreads. This result implies that the inside spread fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
231
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(242 citation statements)
references
References 8 publications
9
231
2
Order By: Relevance
“…In a similar vein, Christie and Huang (1994) and Barclay (1997) find that trading costs decrease after stocks move from the NASDAQ to the NYSE. Others with similar findings include Goldstein (1993), Christie and Schultz (1994), Bessembinder (1999Bessembinder ( , 2003, and Chung et al (2001).…”
mentioning
confidence: 69%
“…In a similar vein, Christie and Huang (1994) and Barclay (1997) find that trading costs decrease after stocks move from the NASDAQ to the NYSE. Others with similar findings include Goldstein (1993), Christie and Schultz (1994), Bessembinder (1999Bessembinder ( , 2003, and Chung et al (2001).…”
mentioning
confidence: 69%
“…In this paper, we find that individual film critics exhibit a statistical bias toward specific studios. Perhaps the best analog to these findings in a very different context would be the study by Christie and Schultz (1994). Christie and Schultz (1994) found that odd eighth quotes were virtually non-existent for 70 out of the 100 actively traded stocks in the Nasdaq.…”
Section: Conclusion and Discussionmentioning
confidence: 98%
“…Perhaps the best analog to these findings in a very different context would be the study by Christie and Schultz (1994). Christie and Schultz (1994) found that odd eighth quotes were virtually non-existent for 70 out of the 100 actively traded stocks in the Nasdaq. They interpreted their results as evidence of collusion by market makers to keep spreads wider.…”
Section: Conclusion and Discussionmentioning
confidence: 98%
“…costs between the NYSE and NASDAQ (e.g., Christie and Schultz 1994;Huang and Stoll 1996;Bessembinder and Kaufman 1997;Chung et al 2001) accompany investigations of cream-skimming, purchased order flow, and preferencing (e.g., Easley et al 1996;Battalio 1997;Chung et al 2004). Another stream of research concentrates on competition between market centers engaged in trading of listed securities (e.g., Lee 1993;Blume and Goldstein 1997;Bessembinder 2003;Barclay et al 2003;Goldstein et al 2008).…”
mentioning
confidence: 99%